Manajemen Reaksi Anafilaksis - ; Atika Indah Sari (Syntax Idea)
Anaphylaxis is a systemic hypersensitivity reaction involving multiple organs, one or more airways, breathing, or circulation problems. Anaphylaxis is potentially life-threatening and must be recognized, managed, and prevented by all healthcare professionals. Management of anaphylactic reactions needs to be done quickly and precisely to reduce the risk of mortality in patients. Intramuscular administration of epinephrine is the first-line therapy for anaphylactic reactions. Patients must recognize and avoid the allergens that precipitate anaphylactic reactions to prevent anaphylactic recurrence in the future.